Project Management ToolBox : Tools and Techniques for the Practicing Project Manager. - Snyder Dionisio, Cynthia (John Wiley & Sons, Incorporated, 2025)
Comprehensive, on-the-go toolkit for professional project managers, updated to reflect the tools necessary for today's predictive, adaptive, hybrid work environment Project Management ToolBox is a go-to reference for on-the-job project managers and advanced students of project management, providing a contemporary set of tools and explaining each tool's purpose and intention, development, customization and variations. Examples, tips, and variations guide readers through the application of these tools. The Third Edition, led by bestselling project management author Cynthia Snyder Dionisio, has been updated to offer a contemporary set of tools to reflect changes in project management learning and practice. This edition includes several new chapters that reflect today's predictive, adaptive, and hybrid work environment. New content includes the project canvas, project roadmap, procurement strategy, risk responses, and more. The book is structured to follow the flow of projects, starting with project selection, project origination, planning, implementation, monitoring, and closure. Within each section there is a wealth of tools, examples, tips, and variations to tailor the use of the tools. Sample topics covered in Project Management ToolBox include: Economic methods, such as payback time, net present value, and internal rate of return. Identifying, analyzing, and communicating with project stakeholders. Plans for eliciting, managing, and specifying requirements, along with a matrix to tracing requirements. Work breakdown structures, network diagrams, critical path method, and critical chain method. Exploring emerging topics within the world of project management and keeping up to date on the latest, most relevant subject areas, Project Management ToolBox is a must-have resource that enables project managers to improve outcomes, deliver quality products and meet stakeholder expectations.
Keywords: Project management.; elektronické knihy; electronic books